Challenges of compiling a parallel corpus - Gulhida Hakimova Abdulaziz qizi; Anorkhon Akhmedova Nasibaliyevna (Zien Journals, 2022)
This article is aimed to feature parallel corpus and the process of compiling it. In particular, the main focus of interest is the challenges that a compiler can come across during the creation of a parallel corpus.
Keywords: Corpus Linguistics; Parallel Corpus; Copyright; Custom Interface